Analysis Of Patient Satisfaction With Low Back Pain Who Received Treatment At Morowali Hospital - Andy Rahman Mujito; Yuli Peristiovati; Novita Anna (Journal for Quality in Public Health, 2024)
Hospital RSUD Morowali is a governmant issued hospital morowali built since the 2003 budget year through dana DHS-ADB, APBN and APBD with lots of land 5 Ha and the spacious building 5.155,48 m2. The existence oregional task force (SKPD) RSUD Morowali in accordance with the regentsrule Morowali Number :188.3/0930/RSUD/2008 October 17, 2008 RSUD Morowali it’s been working since 2006 and has received permission from central Sulawesi provincial health services Number :445/04.68/DINKES l 27 Februari 2008. The purpose of this study is to explore the satisfaction of patients with low back pain who come for treatment at Morowali Hospital and get achronology of problems from the observation results, namely 1) Exploring patients with low back pain who are treated at Morowali Hospital? 2) Exploring patient satisfaction who are treated at Morowali Hospital? a). Exploring the services of officers (nurses, doctors, physiotherapists) b). exploring the completenes of management tools and physiotherapy tools Lbp c). Exploring the treatment provided (nurses, doctors, physiologists). This study uses qualitative research techniques such as sampling, observation, in- depth interviews and documentation. Then the data is analyzed, data presented, and conclusions drawn. The results of the research that have been obtained are generally satisfied with patients who come for treatment at the Morowali Regional General Hospital (RSUD) but they are constrained by the cost of physiotherapy treatment because the physiotherapy treatment in the hospital is not affordable and they decide not to do continuous therapy because of the cost constraints and the patient concludes that the treatment they are doing is not There is change and dissatisfaction     Keywords: hospital, low back pain, satisfaction